Prospect of Rice Estate Development in Merauke Regency: A View from Soil and Water Management Aspects - I GUSTI MADE SUBIKSA (Jurnal Sumberdaya Lahan, 2008)
Rice estate development as instrument is targeting Merauke as a rice basket in the eastern part of Indonesia has been started by completing of Master Plan of Rice Estate Development. In the Master Plan, 206 cluster of production zone has been delineated, where each cluster consisted of about 5,000 ha. Rice estate development requires the appropriate land and water management planning to reach high land productivity and sustainable agriculture with minimal negative impacts to the environment. The appropriate soil and water management technologies are believed as key factors to develop this region, because most of the potential lands were swampy. The flat topography with unique and various climatic and hydrological characteristis lead to local specific land and water management. Site plan design model of rice estate should be integrated rice base crop livestock system. Since ruminant could make sinergic interaction with rice, the external input will be lower for sustainable agriculture. Amelioration, balance fertilization, and organic matter management will become technological components to determine the success of rice estate development. This paper explains the prospect of rice estate development from the view point of land and water management, organic matter, and balance fertilization in Merauke Regency, Papua.